2018
DOI: 10.3389/fimmu.2018.01028
|View full text |Cite
|
Sign up to set email alerts
|

Association of T and NK Cell Phenotype With the Diagnosis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS)

Abstract: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a pathological condition characterized by incapacitating fatigue and a combination of neurologic, immunologic, and endocrine symptoms. At present its diagnosis is based exclusively on clinical criteria. Several studies have described altered immunologic profiles; therefore, we proposed to further examine the more significant differences, particularly T and NK cell subpopulations that could be conditioned by viral infections, to discern their utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 99 publications
2
50
1
Order By: Relevance
“…Another important function of HLA class I alleles is to serve as ligands for NK cell receptors. Altered numbers and function of NK cells have been reported by several independent researchers in ME/CFS 14,15,40 . The other associated allele, DQB1*03:03, is an HLA class II allele, which is also interesting in regard to the hypothesis of autoimmunity in ME/CFS.…”
Section: Discussionmentioning
confidence: 84%
“…Another important function of HLA class I alleles is to serve as ligands for NK cell receptors. Altered numbers and function of NK cells have been reported by several independent researchers in ME/CFS 14,15,40 . The other associated allele, DQB1*03:03, is an HLA class II allele, which is also interesting in regard to the hypothesis of autoimmunity in ME/CFS.…”
Section: Discussionmentioning
confidence: 84%
“…Baseline T cell proliferation was lower than controls, and post-vaccination proliferation was higher in ME/CFS patients compared to controls, although these findings were not statistically significant. Lower proliferative responses were observed among other ME/CFS patients as well [ 220 ], and decreased cytotoxicity of NK and T cells [ 217 ], as well as increased levels of cytokine producing CD56bright NK cells [ 221 ], have been documented, although findings have not been consistently confirmed between studies.…”
Section: Molecular Mechanisms Behind Viral Pathogenesis In Me/cfsmentioning
confidence: 99%
“…Cytokines reported to be altered in abundance include TNF-α, TGF-β, IFN-γ, IL-1α, IL-1β, IL-6, and IL-4 (1,(5)(6)(7)(8)(9)(10). Some studies have also reported differences in the frequency of CD4 + versus CD8 + T cells, Tregs, and/or memory T cells in patients with ME/CFS (10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%